2005
DOI: 10.1007/s00441-004-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evidence identifying the site of androgen production in the ovary of the protogynous grouper Epinephelus merra

Abstract: Androgen plays an important role in the developing ovaries of female fish. However, little is known regarding either the sites of production of androgen or its functional roles. In the present study, we investigated immunohistochemically the localization of cholesterol-side-chain-cleavage (P450scc) and cytochrome P45011beta-hydroxylase (P45011beta) with antibodies P450scc and P45011beta in the ovary of the female honeycomb grouper Epinephelus merra during its reproductive cycle. Clusters of strongly immunoposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 35 publications
2
18
0
2
Order By: Relevance
“…Together with histological observation, these results further strengthen our conclusion that the function of FSH is to induce gonadal sex change and spermatogenesis by stimulating androgen production. Previously, we observed that cell clusters immunostained with antibodies to P450 11b-hydoroxylase, which is the key steroidogenic enzyme for production of 11KT, were localized around blood vessels in the tunica albuginea of the ovary [59]. Based on this observation and data from the present study, we hypothesize that FSH acts on these cell clusters at the beginning of the sex change process to stimulate 11KT production.…”
Section: Expression Of Gth Subunits In Protogynous Groupersupporting
confidence: 83%
“…Together with histological observation, these results further strengthen our conclusion that the function of FSH is to induce gonadal sex change and spermatogenesis by stimulating androgen production. Previously, we observed that cell clusters immunostained with antibodies to P450 11b-hydoroxylase, which is the key steroidogenic enzyme for production of 11KT, were localized around blood vessels in the tunica albuginea of the ovary [59]. Based on this observation and data from the present study, we hypothesize that FSH acts on these cell clusters at the beginning of the sex change process to stimulate 11KT production.…”
Section: Expression Of Gth Subunits In Protogynous Groupersupporting
confidence: 83%
“…Recently, clusters of steroid-producing cells in the tunica of fish ovary have been detected as the site for biosynthesis of 11-KT [64] in support of this possibility. In addition, crosstalk between the AR and ER pathways has been suggested, through soluble and membrane receptors as a mechanism for dual involvement of both steroids.…”
mentioning
confidence: 80%
“…In many sexchanging fish, the levels of circulating 11-KT have been reported to increase with the progression of sex change (Nakamura et al 1989;Johnson et al 1998;Kroon and Liley 2000;Bhandari et al 2003), and exogenous 11-KT treatment can induce sex reversal (Kroon and Liley 2000;Yeh et al 2003). It was found that the androgen-producing sites exist in the ovary of honeycomb grouper (Alam et al 2005) and that naturally occurring sex change is accompanied by significant increases in the size of androgen-producing cells and production of androgen by the gonads . The data suggest that androgens play an important role in fish sex change.…”
Section: Endocrine Changes and Regulation During Sex Change Of Groupersmentioning
confidence: 99%